Junction City Photographer J.J. Pennell - John Pultz (Symphony in the Flint Hills, 2013)
A collection of historical images depicting scenes at Ft. Riley and Junction City with a biography of Joseph Judd Pennell.
Keywords: photography; picture; image; historical; horses; Ft. Riley; cavalry; stables; troops; soldiers; Junction City; J.J. Pennell; glass-plate; dry-plate; gelatin-silver; prints; cameramen; studio; technology; portraits; Parade Field; commercial